USE OF THE SCANNER TO PRODUCE IMAGES OF MACROSTRUCTURE - A. G. Anisovich; I. N. Rumyantseva (Литьë и металлургия)
The possibility of obtaining images of macrostructure of metals and nonmetallic materials by means of scanner is considered. Comparison of quality of the images received with the help of scanner and digital camera is carried out. Examples of the quantitative analysis of macrostructure images are given.